2013
DOI: 10.1111/anzs.12059
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Spatial Analysis for the Evaluation of Breast Cancer Detection Methods

Abstract: This study investigated the impact of spatial location on the effectiveness of populationbased breast screening in reducing breast cancer mortality compared to other detection methods among Queensland women. The analysis was based on linked population-based datasets from BreastScreen Queensland and the Queensland Cancer Registry for the period of 1997-2008 for women aged less than 90 years at diagnosis. A Bayesian hierarchical regression modelling approach was adopted and posterior estimation was performed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Women in professional occupations [ 67 , 68 ] and those living in the most advantaged areas [ 68 72 ] had higher survival. Two studies also reported this trend but reported non-significance at the individual [ 66 ] and area level [ 66 , 73 ] after statistical attenuation.…”
Section: Resultsmentioning
confidence: 99%
“…Women in professional occupations [ 67 , 68 ] and those living in the most advantaged areas [ 68 72 ] had higher survival. Two studies also reported this trend but reported non-significance at the individual [ 66 ] and area level [ 66 , 73 ] after statistical attenuation.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have examined the impact of mammographic screening upon individual patient survival. Analyses of survival include examinations of interval cancers (cancers diagnosed following a normal mammogram but prior to the next screening invitation), comparisons of women in dichotomous groups (attenders vs. never‐attenders and those with screen‐detected vs. non‐screen‐detected cancers) and spatial analyses . A review conducted in the UK in 2003 concluded that a better understanding of the effect of screen‐detection required more detailed data.…”
mentioning
confidence: 99%
“…Analyses of survival include examinations of interval cancers 4,5 (cancers diagnosed following a normal mammogram but prior to the next screening invitation), comparisons of women in dichotomous groups (attenders vs. never-attenders 6 and those with screen-detected vs. non-screen-detected cancers 7 ) and spatial analyses. 8 A review conducted in the UK in 2003 9 concluded that a better understanding of the effect of screendetection required more detailed data. In particular, the review identified the importance of linkage of mortality data to screening invitations so that the outcome for tumours diagnosed after the introduction of screening might be examined.…”
mentioning
confidence: 99%
“…The total number of subgroups was allowed to range from J = 2 to 6. The upper bound of 6 was chosen based on previous studies that SLAs can be collapsed into 4–5 spatial regions based on their geographic characteristics such as socio-economic status and area remoteness index [ 3 , 17 , 18 ]. Each mixture subgroup of excess hazard was assigned a mixing probability of π j where 0 < π j < 1 and .…”
Section: Methodsmentioning
confidence: 99%